Embedded Control System for Smart Walking Assistance Device - Bosnak, Matevz; Skrjanc, Igor (IEEE transactions on neural systems and rehabilitation engineering, 2017)
This paper presents the design and implementation of a unique control system for a smart hoist, a therapeutic device that is used in rehabilitation of walking. The control system features a unique human-machine interface that allows the human to intuitively control the system just by moving or rotating its body. The paper contains an overview of the complete system, including the design and implementation of custom sensors, dc servo motor controllers, communication interfaces and embedded-system based central control system. The prototype of the complete system was tested by conducting a 6-runs experiment on 11 subjects and results are showing that the proposed control system interface is indeed intuitive and simple to adopt by the user.